1971
DOI: 10.1063/1.1675589
|View full text |Cite
|
Sign up to set email alerts
|

9Be Quadrupole Perturbed NMR Study of the Ferroelectric Transition in Deuterated Triglycine Fluoberyllate

Abstract: The quadrupole perturbed magnetic resonance spectra of 9Be in a deuterated triglycine fluoberyllate single crystal have been studied as a function of temperature and crystal orientation, and the electric field gradient (EFG) tensors at the Be sites have been determined in the para- and in the ferroelectric phase. The data show that the main effect of the ferroelectric transition is a shift of the Be ion away from the twofold b axis where it lies in the paraelectric phase and a rotation of the two minor princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The temperature dependence of the resonance positions, presented in Fig. 1 for our protonated specimen, is compatible with 9 Be results published for a deuterated crystal [33]. Our measurements nicely document the line splitting occurring for T 5T C : Then spin-alignment spectra were recorded.…”
Section: Quadrupolar Beryllium Spin Alignment In Triglycine Fluoberylsupporting
confidence: 61%
See 2 more Smart Citations
“…The temperature dependence of the resonance positions, presented in Fig. 1 for our protonated specimen, is compatible with 9 Be results published for a deuterated crystal [33]. Our measurements nicely document the line splitting occurring for T 5T C : Then spin-alignment spectra were recorded.…”
Section: Quadrupolar Beryllium Spin Alignment In Triglycine Fluoberylsupporting
confidence: 61%
“…From the cited NMR investigations it was concluded that the rotation rate of the fluoberyllate tetrahedra is in the fast-motion regime much above the phase transition temperature ðT ¼ T C Þ and that it is in the slow-motion regime for T 5T C : The Be atoms were reported to shift concomitantly with respect to their high-temperature positions and the proton transfer within the N-H Á Á Á F bonds connecting the glycines with the BeF 2À 4 groups ceases at low temperatures. However, no information seems to be available regarding the time scale of motions which modulate the EFG tensor at the Be site [19,33].…”
Section: Quadrupolar Beryllium Spin Alignment In Triglycine Fluoberylmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown by Blinc et al [7], TGFB close to the Curie point reveals a marked anomaly of the electric field gradient causing, in our case, a change in zero splitting of the spin energy-levels [l].…”
Section: Effect Of Temperature and High Pressure On The Epr Spectrummentioning
confidence: 87%